Clinical activity of 9-ING-41, a small molecule selective glycogen synthase kinase-3 beta (GSK-3β) inhibitor, in refractory adult T-Cell leukemia/lymphoma. Issue 1 (31st December 2022) - Hsu, Andrew; Huntington, Kelsey E.; De Souza, Andre; Zhou, Lanlan; Olszewski, Adam J.; Makwana, Nirav P.; Treaba, Diana O.; Cavalcante, Ludimila; Giles, Francis J.; Safran, Howard; El-Deiry, Wafik S.; Carneiro, Benedito A.
ABSTRACT: GSK-3β is a serine/threonine kinase implicated in tumorigenesis and chemotherapy resistance. GSK-3β blockade downregulates the NF-κB pathway, modulates immune cell PD-1 and tumor cell PD-L1 expression, and increases CD8 + T cell and NK cell function. We report a case of adult T-cell leukemia/lymphoma (ATLL) treated with 9-ING-41, a selective GSK-3β inhibitor in clinical development, who achieved a durable response. A 43-year-old male developed diffuse lymphadenopathy, and biopsy of axillary lymph node showed acute-type ATLL. Peripheral blood flow cytometry revealed a circulating clonal T cell population, and CSF was positive for ATLL involvement. After disease progression on the 3 rd line of treatment, he started treatment with 9-ING-41 monotherapy in a clinical trial (NCT03678883). CT imaging after seven months showed a partial response. Sustained reduction of peripheral blood ATLL cells lasted 15 months. Treatment of patient-derived CD8 + T cells with 9-ING-41 increased the secretion of IFN-γ, granzyme B, and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL). In conclusion, treatment of a patient with refractory ATLL with the GSK-3β inhibitor 9-ING-41 resulted in a prolonged response. Ongoing experiments are investigating the hypothesis that 9-ING-41-induced T cell activation and immunomodulation contributes to its clinical activity. Further clinical investigation of 9-ING-41 for treatment of ATLL is warranted.